2008
DOI: 10.2528/pier08011102
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS OF WAVE FUNCTION, ENERGY AND TRANSMISSION COEFFICIENTS IN GaN/ALGaN SUPERLATTICE NANOSTRUCTURES

Abstract: Abstract-Analysis of wave function intensity, eigen energy and transmission coefficients in GaN/AlGaN superlattice nanostructure has been carried out using Transfer Matrix Method (TMM). The effect of change in Aluminum mole fraction in Al x Ga 1−x N barrier region has been included through variable effective mass in the Schrödinger time independent equation. The behaviour of wave function intensity has been studied for superlattice structure by changing the barrier width. The effect of smaller barrier width on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…However, their use for clinical applications is limited by their low repetition rates in the range of tens of Hz, the high cost and the bulky size that are mainly due to the power supply and cooling elements [8]. On the other hand, HPDLs [9][10][11] could be an alternative to overcome all these limitations of solid state lasers for OAI, due to their small size, low cost, availability in a wide range of near-infrared (NIR) wavelengths [12][13][14][15], and high repetition rates (kHz) for a fast signal acquisition [16,17]. Although HPDLs offer several advantages compared to other lasers, their output power is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…However, their use for clinical applications is limited by their low repetition rates in the range of tens of Hz, the high cost and the bulky size that are mainly due to the power supply and cooling elements [8]. On the other hand, HPDLs [9][10][11] could be an alternative to overcome all these limitations of solid state lasers for OAI, due to their small size, low cost, availability in a wide range of near-infrared (NIR) wavelengths [12][13][14][15], and high repetition rates (kHz) for a fast signal acquisition [16,17]. Although HPDLs offer several advantages compared to other lasers, their output power is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…The SPPs are electromagnetic surface waves that propagate along the metal-dielectric interface, and they are non-radiative [7]. Because the electromagnetic fields are localized and enhanced on the metal surface when the SPPs are excited, the SPPs have been widely applied in the sub-wavelength optics and plasmonics [8][9][10][11][12][13]. It is well known that the metal plates and films reflect and absorb the emitting light in ordinary light-emitting diodes (LEDs), but a metal plate with narrow slit array can be light-transparent by the excitation of the EOT in some wavelength regions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the quantum structures, quantum well is extensively researched in the last decade because of computational advantages [16][17][18] and also eases of fabrication [19]. Multiple quantum well structures are subject to theoretical and experimental research in last two decades because of the resonant tunneling phenomenon [20], and novel photonic devices are already designed as transmiter [21] and receiver [22] applicable in nanoelectronic domain.…”
Section: Introductionmentioning
confidence: 99%
“…Result showed that remarkable reduction of spin relaxation time can be obtained (4-0.3 ns) when the quantum well structure is subjected under external electric ield applied along the direction of well width at room temperature. To understand the electronic and optical properties of the nanostructures, computation of their eigenstates is very essential along with density of states proile [16]. Among the quantum structures, quantum well is extensively researched in the last decade because of computational advantages [7,8,67] and also eases of fabrication [9].…”
Section: Introductionmentioning
confidence: 99%